The symmetry and asymmetry of pedestrian route choice. (May 2023) - Montello, Daniel R.; Davis, Rie C.; Johnson, Mike; Chrastil, Elizabeth R.
Abstract: During everyday activities, people sometimes take a different route in one direction than they do on the return trip. Yet we do not fully understand the degree to which people choose particular routes, and this asymmetry has yet to be systematically quantified. To address these questions, we designed a multi-segment route on a college campus that included two pairs of reciprocal segments, in which young adult participants (n = 52, ages 18–23, 36f/16m) walked from place A to place B and then later in the route—without being alerted to its reciprocal nature—went from place B to A. We used GPS tracking to record the routes our participants walked, and we developed novel continuous measures of route dissimilarity which we used to analyse both reciprocal and nonreciprocal routes. Our results indicate that there is substantial asymmetry in route choice but no consistent tendency for individual participants to take symmetric or asymmetric routes. We also found substantial variation across participants in the route taken across all segments, but this natural variability in routes did not entirely explain the asymmetries we observed, suggesting that there is systematic asymmetry in route choice that goes over and beyond the tendency simply to take variable routes. Overall, our controlled test of route choice balanced experimental control with ecological validity. Combined with our novel measures of route (dis)similarity, these findings provide a new perspective on this classic route choice problem. Highlights: Controlled but ecologically valid experiment on pedestrian route-choice symmetry. Novel quantification of route-choice symmetry/similarity as continuous metrics. Substantial asymmetry unexplained solely by general route-choice variation. No consistent trait to take symmetric or asymmetric routes.